Los reyes: el laberinto entre mito e historia - Laurentiis , Antonella De (Amaltea. Revista de Mitocrítica, 2009)
In 1977, during a TV interview, Cortázar stated that his book Los reyes appeared in his mind all of a sudden, as if an archetypal memory was surfacing to consciousness. Like a lightning bolt, what he considered to be the real interpretation of the myth of the Minotaur and his labyrinth appeared to him: the story of the monster being killed by the hero was substituted by a picture of the poet being excluded from and imprisoned by power. Moving away from Cortázar’s explanation of his own work, the current paper provides an interpretation of Los reyes that takes into account its historical and political context.